Theoretical investigation on molecular structure of a new mononuclear copper(II) thiocyanato complex with tridentate Schiff base ligand. Issue 22 (17th November 2017) - Thakurta, Santarupa; Butcher, Ray J.; Frontera, Antonio; Mitra, Samiran
Abstract: An asymmetrical Schiff base ligand, 4-bromo-2-(2-pyridylmethyliminomethyl)phenol (HL), and its copper(II) complex, [Cu(L)SCN] (1 ), have been synthesized. Complex1 is experimentally characterized by elemental analysis, FT-IR and UV–vis spectroscopic techniques, and cyclic voltammetry. The structure of the complex has been established by single-crystal X-ray diffraction studies, which reveal a square planar geometry of the central copper(II) ion in1 . The neighboring molecules of the complex connect each other by π–π stacking interactions with centroid-to-centroid ring distance 3.653 Å. The ligand can display two possible tautomeric forms; therefore, 1 can have an alternate molecular structure. DFT calculations have been employed to investigate the structure and relative stabilities of the suggested tautomeric forms of the ligand and its corresponding copper(II) complex. Abstract :